ANALISIS HUBUNGAN VOLUME, KECEPATAN DAN KEPADATAN LALU LINTAS DENGAN METODE GREENSHIELD DAN GREENBERG PADA RUAS JALAN KAPTEN A RIVAI KOTA PALEMBANG - Ivansyah, Wahyu Wandiarto; Wahab, Wahyuni (Ensiklopedia of Journal, 2025)
Traffic congestion is a major problem in developing urban areas, including Palembang City, which is experiencing rapid economic and population growth. Jalan Captain A Rivai, as one of the main routes in Palembang, experiences high traffic volumes but this is not balanced by adequate road capacity, causing congestion, especially during rush hour. This research aims to analyze the relationship between volume, speed and traffic density on Jalan Captain A Rivai using two mathematical models, namely the Greenshield model and the Greenberg model. The analysis results show that the highest volume based on the Greenshield model is 2445.28 smp/hour and 6717.56 smp/hour with Greenberg. The top speed using Greenshield is 31.38 km/h and 22.09 km/h with Greenberg. The highest density reached 115.60 smp/km with Greenshield and 685.20 smp/km with Greenberg. Based on this analysis, the Greenshield method is more appropriate for describing traffic conditions in the field. It is hoped that this research can provide input in traffic management in Palembang City. Keywords: Greenshield model and Greenberg model